Ocular effects and current scenario of pterygium in urban area of Assam - Datta, Goutam; Namasudra, Jewel (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Introduction: A pterygium is a non-cancerous, fleshy, triangular membrane upon the conjunctiva that can extend through the limbus to cornea. Which may create redness, foreign body sensation, and a feeling of something in the eye. If it grows large enough, it can obstruct vision and require surgical removal. A fleshy, often pink or whitish, slightly raised growth with visible blood vessels. Typically starts in the corner of the eye closest to the nose and grows towards the limbus. It can be a small, inactive lesion or a large, fast-growing one that affects the vision. Aim: This study was to know the Ocular effects and current scenario of pterygiums to provide informative resources, which helps to promote awareness on pterygium in the urban area of Kamrup metropolitan District in North-East state Assam. Methods, Materials and Results: The cross-sectional study was done from June 2025 to September 2025, different eye camps in urban area of Guwahati, Kamrup metropolitan district in Assam. Total 789 patients were examined in the urban camps, out of that patients 198 patients were found with pterygium; either one eye or both eye in both genders. The data were analysed statistically. Out of 198 pterygium sufferers, 123 were male sufferers as well as 75 were female sufferers. In the study it was found that medial pterygium was very common as well as monocular pterygium 147(74.24%) and progressive pterygium117 (59.09%). The study was also revealed that Grade I pterygium 127 (64.14%) were more in urban population of Assam. Conclusion: The scenario of pterygium increased with their age. Sunlight and UV exposures are the causative factors of pterygium development. It may be controlled by using protective ocular equipment and continuous awareness.